The Effects Of Micro-Lecture Approach On Students’ Engagement And Students’ Achievement In Flipped Classroom Environment - Voon, Yeun Ting (2019)
Malaysia higher educational institutions continue to practice a traditional learning method, although there are many innovative and creative teaching pedagogy in recent education. Lack of interactivity between the lecturers and students in the traditional classroom affect the students’ engagement and students’ achievement in the learning environments. The problem of instructors to deliver the videos effectively in a flipped classroom also cause the students unable to focus and understand the important concepts about the topics. Therefore, this research investigated the effects of micro-lecture approach on students’ engagement and students’ achievement in flipped classroom environment. Social constructivism and cognitive load theory of student learning provided a comprehensive theoretical framework. A quasi-experimental design incorporated post-test only and students’ engagement instruments were used with a sample of 80 students who took Information and Communication Technology (ICT) course at a Malaysian University. Students were divided into two groups, quiz-based micro-lecture (experimental group) and discussion-based micro-lecture (control group). Both groups watched and finished the online tasks in different learning platforms. The students watched the video lecture in the selected time before class and then attended the class with active learning activities.